Using social auditing to analyze absenteeism in industrial companies: A case study of the GICA Cement Company, Hamma Bouziane Branch - Hind, Nabti; Fatiha, Bouhrine (The International tax journal, 2025)
This study aims to utilize social auditing to analyze the phenomenon of absenteeism at GICA company, Hamma Bouziane branch, while examining future developments of this phenomenon by forecasting absenteeism indicators for the years 2025-2027 using Power BI software. The analytical descriptive methodology was adopted as the foundation for covering theoretical aspects and collecting and analyzing absenteeism data. The study concluded that social auditing revealed challenges and problems in absenteeism management that require proactive intervention and restructuring of organizational practices. This audit was not limited to current diagnosis only, but extended to future forecasting, where it outlined potential scenarios for employee absenteeism during the period from 2025 to 2027, thereby confirming its role as an effective analytical tool in diagnosing and developing institutional performance.